Composition

By using a composition of multimodal high-density polyethylene and saturated amide, the problem of slip agent oxidation in the production of covers and closures is solved, and a good balance between mechanical properties and slip effect is achieved.

CN119546525APending Publication Date: 2025-02-28BOREALIS AG
View PDF 36 Cites 0 Cited by

Patent Information

Application Number
CN202380053656.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-14
Filing Date
2023-07-13
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

When existing high-density polyethylene resins are used to make covers and closures, although they have good mechanical properties, when adding slip agents to reduce friction coefficients, commonly used slip agents such as erucic acid amide can oxidize, causing taste and odor problems in food or beverages. Meanwhile, alternatives such as saturated amides have poor slipping effects and require time to achieve the required low coefficient of friction.

Method used

Using a multimodal high-density polyethylene and saturated amide slip agent composition, a polymer composition with ideal mechanical properties and good slip effect is prepared by adjusting the composition and production process of the polymer.

Benefits of technology

It achieves a significant reduction in the friction coefficient without affecting the mechanical properties, provides a better performance balance, and can quickly achieve low friction effects, avoiding the smell and odor problems caused by the oxidation of slip agents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005240794980000081
    Figure BDA0005240794980000081
  • Figure BDA0005240794980000151
    Figure BDA0005240794980000151
  • Figure BDA0005240794980000152
    Figure BDA0005240794980000152
Patent Text Reader

Abstract

The present invention provides a polymer composition comprising (i) from 95.0 to 99.95 wt%, relative to the total weight of the polymer composition, of a multimodal high density polyethylene (HDPE) having a density of from 945 to 980 kg / m3 as determined according to ISO 1183 and an MFR2 of from 0.1 to 1.3 g / 10 minutes as determined according to ISO 1133 under conditions of 190 DEG C and a load of 2.16 kg; and wherein the multimodal high density polyethylene comprises at least two components: (A) from 30 to 70 wt%, relative to the total weight of the multimodal high density polyethylene, of a low molecular weight component which is a polyethylene having a density of from 955 to 980 kg / m3 as determined according to ISO 1183 and an MFR2 of from 100 to 600 g / 10 minutes as determined according to ISO 1133 under 190 DEG C and 2.16 kg load conditions; and (B) from 30 to 70 wt%, relative to the total weight of the multimodal high density polyethylene, of a high molecular weight component which is a polyethylene having a density of from 930 to 960 kg as determined according to ISO 1183 and an MFR2 of from 0.0001 to 1.0 g / 10 minutes as determined according to ISO 1133 under conditions of 190 DEG C and a load of 2.16 kg; and (ii) 0.05 to 0.5 wt%, relative to the total weight of the polymer composition, of at least one saturated amide slip agent.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a polymer composition comprising a multimodal high density polyethylene (HDPE) and a saturated amide slip agent, which is suitable for the manufacture of molded articles. The present invention also relates to articles comprising the polymer composition, and the use of the composition for the manufacture of articles. Background Art

[0002] High-density polyethylene (HDPE) is widely used in molding applications due to its excellent combination of processability and mechanical properties. It is well known that the properties of polyethylene are related to density. The higher the density, the better the stiffness, but the impact properties tend to decrease.

[0003] The present invention relates to a composition comprising a high-density polyethylene resin, which is suitable for preparing injection molded articles, especially caps and closures. In particular, the caps and closures of the present invention can be used to close bottles, such as bottles for carbonated beverages and still beverages.

[0004] Caps and closures are usually made from high density polyethylene resins because they have good mechanical properties, such as stiffness. However, it should be understood that compositions designed for such applications also need to have other properties that are convenient to use. In some cases, a lower coefficient of friction is required to facilitate unscrewing the cap or closure. Typically, a lower coefficient of friction is achieved by adding a slip agent. However, this brings a well-known key problem to the final product. Some commonly used slip agents, such as erucamide, although having the desired properties, can oxidize, thereby causing unpleasant tastes and odors to the food or beverage in the container. Therefore, there is a need to find alternatives.

[0005] EP 1278797 proposes a solution to use saturated amides as slip agents, because these amides do not have the problem of oxidation. However, the slip effect of these saturated amides is often poor. In addition, the slip effect is usually time-dependent, and it usually takes a long time to reach the desired low friction coefficient.

[0006] Another solution is to use a permanent slip agent, which is usually a solution based on polydimethylsiloxane (PDMS), which can achieve a slip effect immediately and does not change over time. However, in order to achieve a sufficiently good slip effect, a large amount of PDMS is usually required, which has some disadvantages, including negatively affecting other properties of the composition.

[0007] Another issue is related to sustainability. One possible way to make packaging more sustainable is to reduce its weight, but this requires using materials with a better balance of stiffness and impact properties.

[0008] Therefore, there is a need for new solutions that combine a slip effect with improved mechanical properties. The inventors surprisingly found that by using a saturated amide slip agent together with a multimodal high density polyethylene, a better balance of properties can be achieved. In particular, such a composition can produce an attractive coefficient of friction. Surprisingly, this favorable slip effect can be achieved simultaneously with desirable mechanical properties such as stiffness and impact force. Summary of the invention

[0009] From one aspect, the present invention provides a polymer composition comprising:

[0010] (i) 95.0 to 99.95 wt% of a multimodal high density polyethylene (HDPE) having a density of 945 to 980 kg / m2, measured according to ISO 1183, relative to the total weight of the polymer composition; 3 , and its MFR2 is 0.1 to 1.3 g / 10 min measured according to ISO 1133 at 190°C and 2.16 kg load; and wherein the multimodal high density polyethylene comprises at least two components:

[0011] (A) 30 to 70 wt% of a low molecular weight component polyethylene having a density of 955 to 980 kg / m2, measured according to ISO 1183, relative to the total weight of the multimodal high density polyethylene 3 , and MFR2 is 100 to 600 g / 10 min at 190° C. and 2.16 kg load according to ISO 1133; and

[0012] (B) 30 to 70 wt% of a high molecular weight component polyethylene having a density of 930 to 980 kg, measured according to ISO 1183, and an MFR2 of 0.0001 to 1.0 g / 10 min, measured according to ISO 1133, at 190°C and 2.16 kg load, relative to the total weight of the multimodal high density polyethylene; and

[0013] (ii) 0.05 to 0.5 wt% of at least one saturated amide slip agent, relative to the total weight of the polymer composition.

[0014] Viewed from another aspect the invention provides an article comprising a polymer composition as hereinbefore defined.

[0015] Viewed from another aspect the invention provides the use of a polymer composition as hereinbefore defined in the manufacture of an article, preferably an injection or compression moulded article, such as a cap or closure.

[0016] Detailed description of the invention

[0017] High-density polyethylene (HDPE)

[0018] The polymer of the present invention is a high density ethylene polymer (HDPE). The high density polyethylene can be a homopolymer or a copolymer, but is preferably an ethylene copolymer. An ethylene copolymer refers to a polymer in which most of the weight is from ethylene monomer units (i.e., ethylene accounts for at least 50wt% of the total weight of the copolymer). The proportion of comonomer is preferably no more than 10 mol%, more preferably no more than 5 mol%. However, ideally, the comonomer content in the polymer of the present invention is very low, such as 0.1 to 2.0 mol%, for example 0.1 to 1.0 mol%.

[0019] The other copolymerizable monomers are preferably C3-12 α-olefin comonomers, especially C3-10 α-olefin comonomers, especially monoethylene or polyethylene unsaturated comonomers, especially C3-10-α-olefins, such as propylene, 1-butene, 1-hexene, 1-octene and 4-methyl-pent-1-ene. Particularly preferably, 1-hexene, 1-octene and 1-butene or mixtures thereof, especially 1-hexene and 1-butene, are used. Ideally, there is only one comonomer.

[0020] The polymer of the present invention is multimodal, ie comprises at least two components. The polymer is preferably bimodal.

[0021] Typically, a polyethylene composition comprising at least two polyethylene components is referred to as "multimodal", which are produced under different polymerization conditions and therefore have different (weight average) molecular weights and molecular weight distributions. Thus, in this sense, the high density polyethylene polymer of the present invention is a multimodal polyethylene. The prefix "multi" is related to the number of different polymer components that make up the composition. The polyethylene may also be multimodal in terms of comonomer content.

[0022] The form of the molecular weight distribution curve of such a multimodal polyethylene, ie the appearance of a curve of polymer weight fraction as a function of its molecular weight, will show two or more maxima, or at least be significantly broadened compared to the curves for the individual components.

[0023] For example, if a polymer is produced in a continuous multi-stage process using reactors connected in series and using different conditions in each reactor, the polymer components produced in the different reactors will each have a different molecular weight distribution and weight average molecular weight. When the molecular weight distribution curve of such a polymer is recorded, the individual curves of these components are superimposed into the molecular weight distribution curve of the entire polymer final product, usually resulting in a curve with two or more different maxima.

[0024] The MFR2 of the high density polyethylene of the present invention is 0.1 to 1.3 g / 10 min. The preferred range of MFR2 is 0.3 to 1.3 g / 10 min, more preferably 0.4 to 1.1 g / 10 min, for example 0.5 to 1.0 g / 10 min.

[0025] The MFR of the high-density polyethylene of the present invention is 21 Preferably it is 15 to 90 g / 10 min, for example 20 to 85 g / 10 min, most preferably 30 to 80 g / 10 min.

[0026] The MFR of the high-density polyethylene of the present invention is 21 The flow rate ratio (FRR) of MFR2 is preferably at least 25.0, such as at least 35.0, more preferably at least 45.0. In addition, the MFR 21 The flow rate ratio (FRR) of MFR / MFR2 is preferably not more than 80.0, such as not more than 75.0, more preferably not more than 70.0.

[0027] The density of the polymer is between 945 and 980 kg / m 3 Therefore, the polymer of the present invention is high density polyethylene (HDPE). Preferably, the density of the polymer is 950 to 970 kg / m 3 , more preferably 951 to 965 kg / m 3 , even more preferably 952 to 963 kg / m 3 , for example 953 to 960 kg / m 3 .

[0028] The molecular weight distribution (MWD) of the high density polyethylene of the present invention is preferably 7-30, more preferably 9-25, such as 10-20.

[0029] The high density polyethylene of the present invention usually comprises at least a low molecular weight component (A) and a high molecular weight component (B). In a particularly preferred embodiment, the high density polyethylene is composed of components (A) and (B). The weight ratio of component (A) to component (B) is preferably between 30:70 and 70:30, more preferably 35:65 to 65:35, and most preferably 40:60 to 60:40. In some embodiments, the ratio may be 35 to 60 wt% of component (A) and 40 to 65 wt% of component (B), for example 40 to 55 wt% of component (A) and 45 to 60 wt% of component (B), wherein the wt% value is relative to the gross weight of the multimodal high density polyethylene.

[0030] In a particularly preferred embodiment, the wt % values ​​of components (A) and (B) add up to 100%.

[0031] Component (A) and component (B) can each be an ethylene homopolymer or an ethylene copolymer. An ethylene homopolymer refers to a polymer comprising at least 97 mol% (e.g., at least 98 mol%, particularly at least 99.5 mol%) of ethylene monomer units. The definition of the term "ethylene copolymer" is as described above. Most preferably, component (A) is an ethylene homopolymer and component (B) is an ethylene copolymer.

[0032] The high-density polyethylene of the present invention is usually produced by a multistage process, wherein components (A) and (B) are produced in subsequent stages. In this case, the properties of the component produced in the second step (or subsequent step) of the multistage process can be inferred from the polymer produced separately in a single stage by applying the same polymerization conditions as in the production stage of the component in the multistage process (such as the same temperature, partial pressure of reactants / diluents, suspension medium, reaction time) and using a catalyst that does not contain the polymer produced previously. In addition, the properties of the component produced in the higher stage of the multistage process can also be calculated, for example, based on B. Polymer Processing Conference (Polymer Processing Society), Extended Abstracts and Final Program, Gothenburg, August 19-21, 1997, 4:13 (B. Conference on Polymer Processing (The Polymer Processing Society), Extended Abstracts and Final Program, Gothenburg, August 19to 21, 1997, 4:13).

[0033] Thus, although the products of a multi-stage process cannot be measured directly, the identity of the components produced at the higher stages of such a multi-stage process can be determined by applying one or both of the above methods. Those skilled in the art will be able to select the appropriate method.

[0034] High-density polyethylene produced by a multistage process is also known as an "in-situ" blend. The final product consists of an intimate mixture of polymers from two or more reactors, the different molecular weight distribution curves of these polymers together form a molecular weight distribution curve with a broad maximum or two or more maximum values, that is, the final product is a multimodal polymer mixture.

[0035] The MFR2 of the low molecular weight component (A) is from 100 to 600 g / 10 min, preferably from 125 to 500 g / 10 min, more preferably from 150 to 400 g / 10 min, for example from 200 to 380 g / 10 min.

[0036] The density of component (A) is 955 to 980 kg / m 3 , preferably 960 to 978 kg / m3 , for example 965 to 975 kg / m 3 .

[0037] Component (A) may be an ethylene homopolymer or copolymer. Preferably, component (A) is an ethylene homopolymer.

[0038] The MFR2 of the high molecular weight component (B) is 0.0001 to 1.0 g / 10 min, preferably 0.0005 to 0.5 g / 10 min, more preferably 0.0008 to 0.1 g / 10 min, for example 0.001 to 0.05 g / 10 min.

[0039] The density of component (B) is 930 to 960 kg / m 3 , preferably 932 to 955 kg / m 3 , for example 935 to 950 kg / m 3 .

[0040] Component (B) can be an ethylene homopolymer or copolymer. Component (B) is preferably a copolymer. Preferred ethylene copolymers use α-olefins (e.g., C3-12 α-olefins) as comonomers. Examples of suitable α-olefins include but-1-ene, hex-1-ene, and oct-1-ene. But-1-ene is a particularly preferred comonomer.

[0041] The density difference between the low molecular weight component (A) and the high molecular weight component (B) (denoted as Δ density) is ideally less than 32 kg / m 3 Preferably, the density difference is 1 to 32 kg / m 3 , preferably 5 to 31 kg / m 3 , for example 7 to 30 kg / m 3 .

[0042] The tensile modulus of the multimodal high density polyethylene is preferably between 930 and 1500 MPa, more preferably 940 to 1200 MPa, when measured according to ISO 527-2.

[0043] The notched impact strength of the multimodal high density polyethylene is preferably in the range of 13 to 25 kJ / m when measured according to ISO 179 at 1 eA, +23°C. 2 More preferably, it is between 15 and 20 kJ / m 2 .

[0044] Preparation of high density polyethylene

[0045] The high density polyethylene can be produced by any suitable polymerization process known in the art, using conditions that can produce multimodal (e.g. bimodal) polymer products, preferably using Ziegler-Natta catalyst systems. Typically, two or more stages (i.e. multistage) polymerization processes are used, with different process conditions (e.g. different temperatures, pressures, polymerization media, hydrogen partial pressures, etc.) being adopted in different stages or regions. Preferably, the multimodal (e.g. bimodal) composition is produced by multistage polymerization, e.g. using a series of reactors, optionally adding comonomers, preferably only adding in the reactor for producing higher / highest molecular weight components. Multistage process is defined as a polymerization process, wherein each or at least two polymer components are produced in a separate reaction stage, usually with different reaction conditions in each stage, and in the presence of the reaction product (including polymerization catalyst) in the previous stage, so as to produce a polymer comprising two or more components. The polymerization reaction used in each stage may involve conventional ethylene homopolymerization or copolymerization, such as gas phase, slurry phase, liquid phase polymerization, using conventional reactors, such as loop reactors, gas phase reactors, batch reactors, etc. (e.g. with reference to WO97 / 44371 and WO96 / 18662).

[0046] Preferably, the high density polyethylene is a bimodal high density polyethylene prepared by a two-stage polymerization process.

[0047] The first polymerization stage produces an ethylene homopolymer or an ethylene copolymer, typically an ethylene homopolymer, which is subsequently fed to the second polymerization stage. The second polymerization stage may further produce an ethylene homopolymer or an ethylene copolymer, preferably an ethylene copolymer.

[0048] The first polymerisation stage is preferably a slurry polymerisation step.

[0049] The slurry polymerization is usually carried out in an inert diluent, usually a hydrocarbon diluent, such as methane, ethane, propane, n-butane, isobutane, pentane, hexane, heptane, octane, etc., or a mixture thereof. Preferably, the diluent is a low boiling hydrocarbon having 1 to 4 carbon atoms or a mixture of such hydrocarbons. A particularly preferred diluent is propane, which may contain small amounts of methane, ethane and / or butane.

[0050] The ethylene content in the fluid phase of the slurry may be 1 to 50 mol%, preferably 2 to 20 mol%, and particularly 2 to 10 mol%. The advantage of a high ethylene concentration is that the productivity of the catalyst is increased, but the disadvantage is that more ethylene needs to be recovered than a low concentration.

[0051] The temperature of the first polymerization stage is generally from 60 to 100° C., preferably from 65 to 95° C., more preferably from 70 to 90° C. Excessively high temperatures should be avoided to prevent partial dissolution of the polymer into the diluent and fouling of the reactor. The pressure is generally from 1 to 150 bar, preferably from 40 to 80 bar.

[0052] Slurry polymerization can be carried out in any known reactor for slurry polymerization. Such reactors include continuous stirred tank reactors and loop reactors. Slurry polymerization is particularly preferably carried out in a loop reactor. In these reactors, a circulating pump is used to circulate the slurry along a closed pipeline at high speed. Loop reactors are well known in the art, for example, examples are given in US-A-4582816, US-A-3405109, US-A-3324093, EP-A-479186 and US-A-5391654. Therefore, it is preferred that the first polymerization stage is carried out as slurry polymerization in a loop reactor.

[0053] The slurry can be removed from the reactor continuously or intermittently. The preferred method for intermittent removal is to use a settling leg to first concentrate the slurry and then remove a batch of concentrated slurry from the reactor. The use of settling legs is disclosed in US-A-3374211, US-A-3242150 and EP-A-1310295. Continuous removal techniques are disclosed in EP-A-891990, EP-A-1415999, EP-A-1591460 and WO-A-2007 / 025640. As disclosed in EP-A-1310295 and EP-A-1591460, continuous removal can be combined with an appropriate concentration method. It is preferred to remove the slurry continuously from the first polymerization stage.

[0054] Hydrogen is usually introduced in the first polymerization stage to control the MFR2 of the resulting polymer. The amount of hydrogen required to achieve the desired MFR depends on the catalyst used and the polymerization conditions. When slurry polymerization is carried out in a loop reactor, the molar ratio of hydrogen to ethylene is 100 to 1000 mol / kmol (or mol / 1000 mol), preferably 200 to 800 mol / kmol, to obtain the desired polymer properties.

[0055] The average residence time of the first polymerization stage is generally 20 to 120 minutes, preferably 30 to 80 minutes. As is well known in the art, the average residence time τ can be calculated by the following formula 1:

[0056] Formula 1: Residence time

[0057]

[0058] Among them, V R is the volume of the reaction space (the volume of the reactor in a loop reactor and the volume of the fluidized bed in a fluidized bed reactor), Q o is the volume flow rate of the product stream (comprising polymer product and fluid reaction mixture).

[0059] The production rate can be appropriately controlled by the catalyst feed rate. The production rate can also be influenced by appropriate selection of monomer concentration. The desired monomer concentration can be obtained by appropriately adjusting the ethylene feed rate.

[0060] In the second polymerization stage, ethylene is optionally polymerized with at least one alpha-olefin copolymer in the presence of a catalyst and the ethylene polymer produced in the first polymerization stage. It will therefore be appreciated that the second polymerization stage produces an ethylene polymer which is combined with the ethylene polymer produced in the first stage to form the multimodal high density polyethylene of the present invention. Preferred comonomers have been discussed above, but it should be noted that it is particularly preferred if the at least one alpha-olefin is 1-butene.

[0061] The second polymerisation stage is preferably a gas phase polymerisation step, ie carried out in a gas phase reactor. Any suitable gas phase reactor known in the art may be used, such as a fluidised bed gas phase reactor.

[0062] For gas phase reactors, the reaction temperature used is generally between 60 and 115°C (e.g., 70 to 110°C), the reactor pressure is generally between 10 and 25 bar, and the residence time is generally 1 to 8 hours. The gas used is generally a non-reactive gas such as nitrogen, or a low boiling point hydrocarbon such as propane, and a monomer such as ethylene.

[0063] A chain transfer agent (such as hydrogen) is usually added in the second polymerization stage, and the amount of hydrogen added is preferably 50 to 500 mol per 1,000 mol of ethylene.

[0064] The ratio between the first polymerization stage and the second polymerization stage (ie, slurry polymerization and gas phase polymerization) is generally from 30:70 to 70:30, more preferably from 35:65 to 65:35, most preferably from 40:60 to 60:40.

[0065] Prepolymerization

[0066] Prior to the polymerization step discussed above, a prepolymerization step may be performed. The purpose of prepolymerization is to polymerize a small amount of polymer onto the catalyst at low temperature and / or low monomer concentration. By prepolymerization, the performance of the catalyst in the slurry can be improved and / or the properties of the final polymer can be changed. The prepolymerization step is performed in a slurry.

[0067] Thus, the prepolymerization step can be carried out in a loop reactor. Subsequently, the prepolymerization is preferably carried out in an inert diluent, which is generally a hydrocarbon diluent such as methane, ethane, propane, n-butane, isobutane, pentane, hexane, heptane, octane, etc., or a mixture thereof. Preferably, the diluent is a low boiling hydrocarbon having 1 to 4 carbon atoms or a mixture of such hydrocarbons.

[0068] The temperature of the prepolymerization step is generally from 0 to 90°C, preferably from 20 to 80°C, more preferably from 55 to 75°C.

[0069] The pressure is not critical and is generally between 1 and 150 bar, preferably between 40 and 80 bar.

[0070] In the prepolymerization step, the amount of monomer used is generally such that 0.1 to 1000 grams of monomer can be polymerized per gram of solid catalyst component. As known to those skilled in the art, the catalyst particles recovered from the continuous prepolymerization reactor do not all contain the same amount of prepolymer. On the contrary, each particle has its own characteristic amount, which depends on the residence time of the particle in the prepolymerization reactor. Since some particles stay in the reactor for a relatively long time, while some particles stay for a relatively short time, the prepolymer content on different particles is also different, and the prepolymer content on some particles may exceed the above-mentioned limit. However, the average amount of prepolymer on the catalyst is usually within the range specified above.

[0071] The molecular weight of the prepolymer can be controlled by hydrogen, which is well known in the art. In addition, as disclosed in WO-A-96 / 19503 and WO-A-96 / 32420, antistatic additives can be used to prevent the particles from sticking to each other or to the reactor wall.

[0072] When there is a prepolymerization step, it is preferred that the catalyst components are all introduced into the prepolymerization step. However, if the solid catalyst component and the cocatalyst can be fed separately, only part of the cocatalyst can be introduced into the prepolymerization stage, and the remaining part into the subsequent polymerization stage. Moreover, in this case, it is necessary to introduce enough cocatalyst in the prepolymerization stage to obtain a sufficient polymerization reaction.

[0073] It is to be understood that within the scope of the present invention the amount of polymer produced in the prepolymerisation will generally be from 1 to 5 wt% of the final high density polyethylene.

[0074] catalyst

[0075] The polymerization is usually carried out in the presence of a Ziegler-Natta polymerization catalyst. Suitable Ziegler-Natta (ZN) catalysts usually comprise at least one catalyst component, which is formed by a transition metal compound of Group 4 to Group 6 of the Periodic Table of Elements (IUPAC, Nomenclature of Inorganic Chemistry, 1989), a metal compound of Group 1 to Group 3 of the Periodic Table of Elements (IUPAC), an optional compound of Group 13 of the Periodic Table of Elements (IUPAC), and an optional internal organic compound, such as an internal electron donor. The ZN catalyst may also include other catalyst components, such as a co-catalyst and optional external additives.

[0076] Suitable ZN catalysts preferably comprise a magnesium compound, an aluminum compound and a titanium compound supported on a particulate support.

[0077] The particle support may be an inorganic oxide support, such as a support based on silica, alumina, titania, silica-alumina, silica-titania or MgCl 2. Preferably, the support is a support based on silica or MgCl 2.

[0078] Particularly preferred Ziegler-Natta catalysts are described in EP 1378528 A1 and EP 2994506.

[0079] If a magnesium compound is used, the magnesium compound is preferably the reaction product of a dialkylmagnesium and an alcohol. The alcohol is a linear or branched aliphatic monohydric alcohol. Preferably, the alcohol has 6 to 16 carbon atoms. Branched alcohols are particularly preferred, 2-ethyl-1-hexanol being an example of a preferred alcohol. The dialkylmagnesium can be any compound in which magnesium is bonded to two identical or different alkyl groups. Butyloctylmagnesium is an example of a preferred dialkylmagnesium.

[0080] The aluminum compound is a chlorine-containing alkyl aluminum. Particularly preferred compounds are alkyl aluminum dichloride and alkyl aluminum sesquichloride.

[0081] The transition metal compound of Groups 4 to 6 is preferably a titanium or vanadium compound, more preferably a halogen-containing titanium compound, and most preferably a chlorine-containing titanium compound. A particularly preferred titanium compound is titanium tetrachloride.

[0082] The catalyst can be prepared by contacting the support with the above compounds in sequence, as described in EP 688794 or WO 99 / 51646. Alternatively, the components can be prepared as a solution and then contacting the solution with the support, as described in WO 01 / 55230.

[0083] Another group of suitable ZN catalysts contains a titanium compound and a magnesium halide compound as a support. Thus, the catalyst contains a titanium compound and optionally a Group 13 compound, for example, an aluminum compound on a magnesium dihalide, such as an aluminum compound on magnesium dichloride. For example, such catalysts are disclosed in WO 2005 / 118655, EP 810235, WO 2014 / 096296 and WO 2016 / 097193.

[0084] Suitable activators are Group 13 metal compounds, typically Group 13 alkyl compounds, particularly alkylaluminum compounds, wherein the alkyl group contains 1 to 16 carbon atoms. These compounds include trialkylaluminum compounds, such as trimethylaluminum, triethylaluminum, triisobutylaluminum, trihexylaluminum and tri-n-octylaluminum; alkylaluminum halides, such as ethylaluminum dichloride, diethylaluminum chloride, ethylaluminum trichloride, dimethylaluminum chloride, etc. Particularly preferred activators are trialkylaluminums, of which triethylaluminum, trimethylaluminum and triisobutylaluminum are particularly useful.

[0085] The amount of activator used depends on the specific catalyst and activator. Typically, triethylaluminum is used in an amount such that the molar ratio of aluminum to transition metal such as Al / Ti is 1 to 1000, preferably 3 to 100, particularly about 5 to 30 mol / mol.

[0086] The optional internal organic compound may be selected from the following classes: ethers, esters, amines, ketones, alcohols, anhydrides or nitriles or mixtures thereof. Preferably, the optional internal organic compound is selected from ethers and esters, most preferably from ethers. Preferred ethers have 2 to 20 carbon atoms, particularly mono-, di- or polycyclic saturated or unsaturated ethers containing 3 to 6 ring atoms. Typical cyclic ethers suitable for the present invention, if used, include tetrahydrofuran (THF), substituted tetrahydrofurans (such as 2-methyltetrahydrofuran), bicyclic ethers (such as 2,2-bis(2-tetrahydrofuranyl)propane, 2,2-bis(2-furanyl)propane) or isomers or mixtures thereof. The internal organic compound is sometimes also referred to as an internal electron donor.

[0087] When producing the high density polyethylene of the present invention, a compounding step is preferably used, wherein the base resin composition, ie the blend obtained from the reactor usually in the form of base resin powder, is extruded in an extruder and then pelletized into polymer particles in a manner known in the art.

[0088] The high-density polyethylene may also contain a small amount of additives, such as pigments, nucleating agents, antistatic agents, fillers, antioxidants, etc., the content of which generally does not exceed 10% by weight, preferably does not exceed 5% by weight.

[0089] Optionally, in the mixing step, additives or other polymer components may be added to the high density polyethylene in the above amounts. Preferably, the high density polyethylene of the present invention obtained from the reactor is mixed with the additives in an extruder in a manner known in the art.

[0090] Composition

[0091] The present invention relates to a composition comprising a high density polyethylene as defined above and at least one saturated amide slip agent.

[0092] The polymer composition comprises 95.0 to 99.95 wt% of high-density polyethylene relative to the total weight of the polymer composition. Preferably, the content of high-density polyethylene is preferably 96.0 to 99.92 wt%, more preferably 97.0 to 99.90 wt%, relative to the total weight of the polymer composition.

[0093] The at least one saturated amide slip agent is present in an amount of 0.05 to 0.5 wt % relative to the total weight of the polymer composition. It is preferred if the at least one amide slip agent is present in an amount of 0.08 to 0.4 wt %, more preferably 0.1 to 0.3 wt %, even more preferably 0.12 to 0.25 wt %, relative to the total weight of the polymer composition.

[0094] Although polymers other than high-density polyethylene may be present in the polymer composition within the scope of the present invention, it is preferred if the polymer composition contains only high-density polyethylene as a single polymer component.

[0095] The polymer composition is preferably composed of high-density polyethylene and at least one saturated amide slip agent. For the avoidance of doubt, even if the polymer composition is "composed" of high-density polyethylene and at least one saturated amide slip agent, conventional polymer additives such as pigments, nucleating agents, antistatic agents, fillers and antioxidants may still be present. Therefore, the term "consisting of..." does not mean to exclude the presence of polymer additives. However, the term does exclude the presence of other polymer components blended with high-density polyethylene and at least one saturated amide slip agent. If a carrier polymer is used as part of a masterbatch, the carrier polymer is not excluded. The composition may not contain any other mixed polymers, but may still contain a small amount of carrier polymer for the masterbatch.

[0096] However, in one embodiment, the composition preferably does not include a nucleating agent.

[0097] The polymer composition is typically prepared by blending and intimately mixing the components (eg, high density polyethylene and at least one saturated amide slip agent), such as by melt mixing in an extruder.

[0098] The polymer composition ideally has a coefficient of friction (CoF) of less than 0.3 when measured according to ISO 8295 over 14 days on injection molded specimens prepared according to ISO 17855-2, as described in the Test Methods. The preferred range of CoF is from 0.28 to 0.26, more preferably from 0.10 to 0.26.

[0099] Saturated amide slip agent

[0100] The at least one saturated amide slip agent can be any suitable amide slip agent known in the art. The term "slip agent" is well known to the skilled person, and it is understood that the amide slip agent can be any slip agent comprising at least one amide group. In addition, the amide slip agent is a saturated compound, and the meaning of "saturated" in this context is well known to those skilled in the art. Slip agents are generally used to reduce the force required to remove a closure from a bottle or package.

[0101] In a preferred embodiment, the amide slip agent is a fatty acid amide derivative. Therefore, the slip agent may preferably be a saturated fatty acid amide derivative.

[0102] The saturated fatty acid amide may contain 8 to 30 carbon atoms. The saturated fatty acid amide is preferably a straight chain fatty acid amide, represented by the formula CH3(CH2)nCONH2, wherein n is 6 to 28. Straight chain saturated fatty acid amides containing at least 12 carbon atoms and mixtures thereof are particularly preferred. Most preferably, the saturated fatty acid amide is selected from the group consisting of behenic acid amide, arachidamide, stearic acid amide, palmitamide, myristic acid amide, lauryl amide and mixtures thereof. It is particularly preferred if the saturated fatty acid amide is selected from the group consisting of behenic acid amide, stearic acid amide and mixtures thereof.

[0103] Within the scope of the present invention, the composition may contain a single amide slip agent or a mixture of two or more different amide slip agents. A single saturated amide slip agent is most preferred.

[0104] Products

[0105] In addition, the present invention also relates to a product comprising the above composition. The present invention also relates to the use of the composition in manufacturing products.

[0106] In one embodiment, the article comprises at least 90.0 wt% of the composition of the present invention, more preferably at least 95.0 wt%, still more preferably at least 98.0 wt%, such as at least 99.9 wt%, relative to the total weight of the article. It is particularly preferred that the article consists of the composition.

[0107] The article according to the present invention may be a compression molded or injection molded article, preferably an injection molded article, more preferably a cap or closure. These articles can be prepared by conventional methods known in the art.

[0108] It should be understood that any of the above parameters are measured according to the detailed tests given below. For those parameters that have been disclosed with smaller and larger ranges, their embodiments are disclosed under the premise of being associated with smaller and larger ranges of embodiments of other parameters.

[0109] The invention will now be described with reference to the following non-limiting examples.

[0110] Test method:

[0111] Melt flow rate (MFR)

[0112] Melt flow rate is according to ISO 1133 at 190°C and a load of 2.16 kg (MFR2) or 21.6 kg (MFR 21 ) conditions.

[0113] Calculate the MFR2 of components (A) and (B)

[0114] logA=x·logB+(1-x)·logC

[0115]

[0116] B = MFR2 of component (A)

[0117] C = MFR2 of component (B)

[0118] A = Final MFR2 of multimodal high density polyethylene (blend)

[0119] X = weight fraction of component (A)

[0120] Flow rate ratio (FRR21 / 2)

[0121] FRR is determined as MFR 21 Ratio to MFR2.

[0122] Gel Permeation Chromatography (GPC)

[0123] According to ISO 16014-1:2003, ISO 16014-2:2003, ISO 16014-4:2003 and ASTM D 6474-12, the average molecular weight (Mz, Mw and Mn), molecular weight distribution (MWD) and its width are determined by gel permeation chromatography (GPC), which is described by the polydispersity index, that is, PDI = Mw / Mn (where Mn is the number average molecular weight and Mw is the weight average molecular weight). The formula used is as follows:

[0124]

[0125]

[0126]

[0127] For a constant elution volume interval ΔV i , where A i and Mi is the chromatographic peak slice area and the molecular weight (MW) of polyolefins, both related to the elution volume V i where N is equal to the number of data points obtained from the chromatogram between the integration limits.

[0128] A high temperature GPC instrument was used, equipped with an infrared detector (IR4 or IR5 from PolymerChar (Valencia, Spain)) equipped with three Agilent-PLgel Olexis and one Agilent-PLgelOlexis Guard columns. The solvent and mobile phase were 1,2,4-trichlorobenzene (TCB), stabilized with 250 mg / L 2,6-di-tert-butyl-4-methylphenol. The chromatographic system was operated at 160°C and a constant flow rate of 1 mL / min. 200 μL of sample solution was injected for each analysis. Data collection was performed using Agilent Cirrus version 3.3 software or PolymerChar GPC-IR control software.

[0129] The column set was calibrated using a universal calibration method (according to ISO 16014-2:2003) using 19 narrow MWD polystyrene (PS) standards ranging from 0.5 kg / mol to 11500 kg / mol. The PS standards were dissolved at room temperature for several hours. The conversion of polystyrene peak molecular weights to polyolefin molecular weights was performed using the Mark Houwink equation and the following Mark Houwink constants:

[0130] K PS =19x10 -3 mL / g,α PS =0.655

[0131] K PE =39x10 -3 mL / g,α PE =0.725

[0132] K PP =19x10 -3 mL / g,α PP =0.725

[0133] A cubic polynomial fit was used to fit the calibration data.

[0134] All samples were dissolved in the concentration range of 0.5-1 mg / ml at 160°C for 2.5 hours (polypropylene) or 3 hours (polyethylene) with gentle shaking.

[0135] Comonomer content

[0136] Quantitative analysis of microstructure using NMR spectroscopy

[0137] Quantitative nuclear magnetic resonance (NMR) technology was used to quantitatively analyze the comonomer content of the polymer.

[0138] In the molten state, the NMR spectrometer was used to record the ions at 500.13 and 125.76 MHz. 1 H and 13 Quantification of C 13 C{ 1 H} NMR spectra. All spectra were obtained using 13 A C-optimized 7 mm magic angle spinning (MAS) probe was recorded at 150 °C, with nitrogen used for all pneumatics. Approximately 200 mm of material was loaded into a 7 mm outer diameter zirconium oxide MAS rotor and spun at 4 kHz. This setup was chosen primarily to achieve the high sensitivity required for rapid identification and accurate quantification: {klimke06,parkinson07,castignolles09}. Standard single pulse excitation was used, utilizing the NOE with short recycle delay {pollard04,klimke06} and the RS-HEPT decoupling scheme {fillip05,griffin07}. A total of 1024 (1k) transients were acquired for each spectrum.

[0139] Quantification 13 C{ 1 H} NMR spectra were processed and integrated, and the relevant quantitative properties were determined from the integration. All chemical shifts were internally referenced to the methylene signal (δ+) at 30.00 ppm.

[0140] The ethylene content is quantified by the integration of the methylene (δ+) sites at 30.00 ppm over the number of reported sites for each monomer:

[0141] E=I δ+ / 2

[0142] Correction for the presence of isolated comonomer is made based on the amount of isolated comonomer present:

[0143] E total = E + (3*B + 2*H) / 2

[0144] Where B and H refer to their respective comonomers. If there is continuous and discontinuous comonomer incorporation, corrections are made in a similar manner.

[0145] Characteristic signals corresponding to 1-butene incorporation were observed, and the comonomer fraction was calculated as the fraction of 1-butene in the polymer relative to all monomers in the polymer:

[0146] fBtotal=(Btotal / (Etotal+Btotal+Htotal)

[0147] The amount of isolated 1-butene incorporated into the EEBEE sequence was quantified by the integration of the *B2 site at 38.3 ppm over the number of reported sites per comonomer:

[0148] B=I *B2

[0149] The amount of 1-butene continuously incorporated into the EEBBEE sequence is quantified by the integration of the ααB2B2 sites at 39.4 ppm over the number of reported sites per comonomer:

[0150] BB=2*IααB2B2

[0151] The amount of discontinuously incorporated 1-butene in the EEBEBEE sequence was quantified by the integration of the ββB2B2 sites at 24.7 ppm over the number of reported sites per comonomer:

[0152] BEB=2*IββB2B2

[0153] Since isolated (EEBEE) and discontinuously incorporated (EEBEBEE) 1-butene overlap at the *B2 and *βB2B2 sites, respectively, the total amount of isolated 1-butene incorporated was corrected based on the discontinuous 1-butene content.

[0154] B=I *B2 -2*I ββB2B2

[0155] The total 1-butene content was calculated from the sum of separated, continuously and discontinuously incorporated 1-butene.

[0156] Total B=B+BB+BEB

[0157] The total mole fraction of 1-butene in the polymer is calculated as:

[0158] fB=(Total B / (Total E+Total B+Total H)

[0159] Characteristic signals corresponding to 1-hexene incorporation were observed, and the comonomer fraction was calculated as the fraction of 1-hexene in the polymer relative to all monomers in the polymer:

[0160] fHtotal=(Htotal / (Etotal+Btotal+Htotal)

[0161] The amount of isolated 1-hexene incorporated into the EEHEE sequence was quantified by the integration of the *B4 site at 39.9 ppm over the number of reported sites per comonomer.

[0162] H=I *B4

[0163] The amount of 1-hexene continuously incorporated in the EEHHEE sequence was quantified by the integration of the ααB4B4 sites at 40.5 ppm over the number of reported sites per comonomer.

[0164] HH=2*IααB4B4

[0165] The amount of discontinuously incorporated 1-hexene in the EEHEHEE sequence was quantified by the integration of the ββB4B4 sites at 24.7 ppm over the number of reported sites per comonomer.

[0166] HEH=2*IββB4B4

[0167] The total mole fraction of 1-hexene in the polymer is calculated as:

[0168] fH=(H total / (E total+B total+H total)

[0169] The mole percentage of comonomer incorporation is calculated from the mole fraction:

[0170] B[mol%]=100*fB

[0171] H[mol%]=100*fH

[0172] The weight percent of comonomer incorporation is calculated from the mole fraction:

[0173] B[wt%]=100*(fB*56.11) / ((fB*56.11)+(fH*84.16)+((1-(fB+fH))*28.05))

[0174] H[wt%]=100*(fH*84.16) / ((fB*56.11)+(fH*84.16)+((1-(fB+fH))*28.05))

[0175] References

[0176] Klimke, K., Parkinson, M., Piel, C., Kaminsky, W., Spiess, HW, Wilhelm, M., Macromol. Chem. Phys. 2006; 207:382.

[0177] Parkinson, M., Klimke, K., Spiess, HW, Wilhelm, M., Macromol. Chem. Phys. 2007; 208:2128.

[0178] Pollard, M., Klimke, K., Graf, R., Spiess, H. W., Wilhelm, M., Sperber, O., Piel, C., Kaminsky, W., Macromolecules 2004; 37: 813.

[0179] Filip, X., Tripon, C., Filip, C., J. Mag. Resn. 2005, 176, 239

[0180] Griffin, J. M., Tripon, C., Samoson, A., Filip, C., and Brown, S. P., Mag. Res. in Chem. 2007 45, S1, S198

[0181] Castignolles, P., Graf, R., Parkinson, M., Wilhelm, M., Gaborieau, M., Polymer 50(2009)2373

[0182] Busico, V., Cipullo, R., Prog. Polym. Sci. 26(2001)443

[0183] Busico, V., Cipullo, R., Monaco, G., Vacatello, M., Segre, A. L., Macromoleucles 30(1997)6251

[0184] Zhou, Z., Kuemmerle, R., Qiu, X., Redwine, D., Cong, R., Taha, A., Baugh, D. Winniford, B., J. Mag. Reson. 187(2007)225

[0185] Busico, V., Carbonniere, P., Cipullo, R., Pellecchia, R., Severn, J., Talarico, G., Macromol. Rapid Commun. 2007, 28, 1128

[0186] Resconi, L., Cavallo, L., Fait, A., Piemontesi, F., Chem. Rev. 2000, 100, 1253

[0187] Density

[0188] The density of the sample preparation was measured according to ISO 1183 and ISO 1872-2.

[0189] Tensile modulus

[0190] Tensile properties were determined according to ISO 527-2 on injection molded specimens, specimen type multipurpose bar 1A, 4 mm thickness. Tensile modulus was measured at a speed of 1 mm / min. Sample preparation was carried out according to ISO 17855-2.

[0191] Notched impact strength

[0192] Notched impact strength was measured according to ISO179, conditions were 1eA, +23°C, sample size was 80*10*4mm 3 The sample preparation was carried out according to ISO 17855-2.

[0193] Coefficient of Friction (CoF)

[0194] According to ISO 8295, in 150×80×1mm 3 CoF was measured on thick injection molded specimens. Injection molding was performed in accordance with ISO17855-2. CoF testing was performed on a Zwick Z1.0 S machine. The conditions used were as follows:

[0195] Test speed: 100mm / min±10mm / min

[0196] Measuring distance: 56mm

[0197] Load weight: 200g±2g

[0198] Before measurement, the sample is stored at 23°C and 50% relative humidity for a desired period of time, such as 1 day, 3 days, 7 days, etc.

[0199] experiment

[0200] Material:

[0201] Slip Agent 1: Finawax S, stearamide, available from Fine Organics.

[0202] Slip Agent 2: Finawax B, behenamide, available from Fine Organics.

[0203] Slip Agent 3: Finawax E, erucamide, available from Fine Organics.

[0204] High density polyethylene 1: Bimodal high density polyethylene, produced in a pilot plant with ZN catalyst (as disclosed in EP 2994506), with a prepolymerization-loop-gas phase reactor configuration, having an MFR of 0.8 g / 10 min and a density of 955.5 kg / m 3 .

[0205] High density polyethylene 2: Bimodal high density polyethylene, produced in a pilot plant with ZN catalyst (as disclosed in EP 2994506), with a prepolymerization-loop-gas phase reactor configuration, with an MFR of 1.28 g / 10 min and a density of 962.5 kg / m 3 .

[0206] HDPE 3: Unimodal HDPE, produced in a pilot plant using Lynx 200 catalyst (supplied by GraceCatalysts Technologies) in a prepolymerization-loop reactor configuration, with an MFR of 0.97 g / 10 min and a density of 961.5 kg / m 3 .

[0207] High density polyethylene 4: as described in EP 2402391 and Table 1.

[0208] Table 1 shows typical polymerization parameters and final polymer properties of HDPEs 1, 2, 3 and 4.

[0209] Table 1

[0210]

[0211]

[0212] *ΔDensity = Density (low molecular weight) - Density (high molecular weight)

[0213] Preparation of compositions and test samples

[0214] The required amount of high-density polyethylene powder and additives were premixed in an intensive mixer and then compounded on a ZSK 57 twin-screw extruder. The melt temperature was 210° C. and the production rate was 200 kg / h. The following additives were added: 0.05 wt% of Irganox 1010 (BASF), 0.2 wt% of Irganox 168 (BASF) and 0.05 wt% of CEASIT Fi, where wt% is relative to the total weight of the composition (the sum of high-density polyethylene powder + additives is 100%).

[0215] Five compositions were prepared by blending, as shown in Table 2. The blending was carried out on a ZSK 18 twin-screw extruder with a melt temperature of 210°C and an output of 7 kg / h. 3 The friction coefficient was measured on the injection molded specimens for a series of time periods and the results are shown in Table 2.

[0216] It can be seen that the combination of saturated amide and bimodal high density polyethylene produces sufficient slip effect, at least comparable to that of erucamide in comparative example 1 (CE1) (which has known oxidation problems). Comparative example 2 (CE2) is a combination of unimodal high density polyethylene and saturated amide, and its slip effect is very poor compared to the bimodal high density polyethylene composition of the present invention with the same formulation. In general, the CoF of the inventive examples is lower than 0.3, which meets all requirements. Combining the mechanical properties and the CoF effect, the results show that the inventive examples are the best combination of slip effect and mechanical property improvement.

[0217] Table 2: Composition and properties of molded articles

[0218]

Claims

1. A polymer composition comprising (i) 95.0 to 99.95 wt% of a multimodal high density polyethylene (HDPE) having a density of 945 to 980 kg / m2, measured according to ISO 1183, relative to the total weight of the polymer composition; 3 , and its MFR2 is 0.1 to 1.3 g / 10 min measured according to ISO 1133 at 190°C and 2.16 kg load; and wherein the multimodal high density polyethylene comprises at least two components: (A) 30 to 70 wt% of a low molecular weight component polyethylene having a density of 955 to 980 kg / m2, measured according to ISO 1183, relative to the total weight of the multimodal high density polyethylene 3 , and MFR2 is 100 to 600 g / 10 min at 190° C. and 2.16 kg load according to ISO 1133; and (B) 30 to 70 wt% of a high molecular weight component polyethylene, relative to the total weight of the multimodal high density polyethylene, having a density of 930 to 960 kg, measured according to ISO 1183, and an MFR2 of 0.0001 to 1.0 g / 10 min, measured according to ISO 1133, at 190°C and 2.16 kg load; and (ii) 0.05 to 0.5 wt% of at least one saturated amide slip agent, relative to the total weight of the polymer composition.

2. The polymer composition according to claim 1, wherein The MFR2 of the low molecular weight component (A) of the high density polyethylene is 125 to 500 g / 10 min, preferably 150 to 400 g / 10 min, more preferably 200 to 380 g / 10 min.

3. The polymer composition according to claim 1 or 2, wherein The density of the high-density polyethylene is 950 to 970 kg / m 3 , preferably 951 to 965 kg / m 3 , more preferably 952 to 963 kg / m 3 , even more preferably 953 to 960 kg / m 3 .

4. The polymer composition according to any one of claims 1 to 3, wherein At 190°C and 21.6 kg load, the MFR of the high-density polyethylene 21 15 to 90 g / 10 min, for example 20 to 85 g / 10 min, most preferably 30 to 80 g / 10 min, determined according to ISO 1133.

5. The polymer composition according to any one of claims 1 to 4, wherein The tensile modulus of the high density polyethylene is 930 to 1500 MPa, preferably 940 to 1200 MPa, as measured according to ISO 527-2.

6. The polymer composition according to any one of claims 1 to 5, wherein The notched impact strength of the high-density polyethylene is 13 to 25 kJ / m at 1eA and +23°C as measured according to ISO 179. 2 , preferably 15 to 20 kJ / m 2 .

7. The polymer composition according to any one of claims 1 to 6, wherein The low molecular weight (LMW) component (A) is an ethylene homopolymer.

8. The polymer composition according to any one of claims 1 to 7, wherein The high molecular weight (HMW) component (B) is a copolymer of ethylene and at least one α-olefin comonomer, preferably a copolymer of ethylene and but-1-ene.

9. The polymer composition according to any one of claims 1 to 8, wherein Relative to the total weight of the polymer composition, the high-density polyethylene comprises 35 to 60 wt% of component (A) and 40 to 65 wt% of component (B), preferably 40 to 55 wt% of component (A) and 45 to 60 wt% of component (B).

10. The polymer composition according to any one of claims 1 to 9, wherein The saturated amide slip agent is selected from the group consisting of behenamide, arachidamide, stearamide, palmitamide, myristicamide, lauramide and mixtures thereof, preferably selected from the group consisting of behenamide, stearamide and mixtures thereof.

11. The polymer composition according to any one of claims 1 to 10, wherein Relative to the total weight of the composition, the composition comprises 96.0 to 99.92 wt %, preferably 97.0 to 99.90 wt %, of the high density polyethylene.

12. The polymer composition according to any one of claims 1 to 11, wherein The composition comprises 0.08 to 0.4 wt % of the amide slip agent, preferably 0.1 to 0.3 wt %, more preferably 0.12 to 0.25 wt %, relative to the total weight of the composition.

13. An article comprising the polymer composition of any one of claims 1 to 12.

14. The article of claim 13, wherein: The article is an injection molded or compression molded article, preferably an injection molded article, such as a cap or a closure.

15. Use of a polymer composition as claimed in any one of claims 1 to 12 for the manufacture of an article, preferably an injection moulded or compression moulded article, such as a cap or closure.

Citation Information

Patent Citations

  • Apparatus and method for producing ethylene polymer

    EP0479186A2

  • Procatalyst for ethylene polymer production, method for its preparation and use

    EP0688794A1

  • Polymerization catalyst

    EP0810235A2

  • High solids slurry polymerization

    EP0891990A2

  • Polyethylene composition and method for making shaped objects from same

    EP1278797A1